Biochemical Synthesis of Zinc-Graphene Nano-Composite Using Cassava Leaf Extract (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2025)
This research explores eco-friendly methods for creating zinc–graphene nanocomposites through green synthesis techniques using plant materials. The study used cassava (Manihot esculenta) leaf extract as a natural substance to reduce and stabilise the nanocomposite.  Energy Dispersive X-ray (EDX) spectroscopy were used to identify the elements and stability of the produced material. The EDX analysis demonstrated that the primary elements of the nanocomposite were zinc and carbon from graphene oxide, which measured 44.50% and 20.70%, respectively. The 15.00% oxygen measurement confirmed the existence of graphene oxide within the material. The analysis identified trace elements, including magnesium (3.62%), calcium (7.01%), iron (3.60%), sulphur (2.40%), sodium (2.02%), and potassium (1.15%), which were likely derived from cassava extract or reaction intermediates. These components have the potential to introduce extra catalytic properties as well as biological functions to the material. The research findings confirm the feasibility of sustainable bio-based methods for creating advanced nanomaterials. The research highlights material science's progressive movement towards environmentally sustainable nanotechnology approaches.
Keywords: Green Synthesis; Cassava Leaf Extract; Nanotechnology; Zinc-Graphene Oxide; Nanocomposite